Managing advertising investments in marketing channels. (March 2022) - Karray, Salma; Martín-Herrán, Guiomar; Sigué, Simon Pierre
Abstract: This paper investigates how should manufacturers optimally allocate resources to retailer-initiated (retailer) advertising through cooperative advertising programs and own (manufacturer) advertising in a bilateral monopoly. Retailer advertising stimulates immediate sales but may also harm long-term (post-advertising) demand, whereas manufacturer advertising aims at building brand equity and stimulates both immediate and long-term sales. A game-theoretic model in which a manufacturer and a retailer set pricing and advertising decisions over a two-period planning horizon is developed to account for the differences between manufacturer and retailer advertising. We characterize equilibrium solutions for four advertising scenarios for the manufacturer, ranging from no investment in any advertising activity to undertaking own advertising and supporting retailer advertising simultaneously. Comparing the two players' equilibrium strategies and profits across these scenarios, we find that manufacturers should avoid offering exclusively cooperative advertising programs to retailers. When retailer advertising positively influences long-term sales, manufacturers should offer cooperative advertising supports to retailers in addition to undertaking their own advertising. When retailer advertising negatively affects long-term sales, manufacturers can still undertake own advertising and offer cooperative advertising under certain conditions. However, if these conditions are not met, focusing exclusively on own advertising is their best advertising strategy. Retailers also prefer scenarios in which manufacturers advertise, but may choose not to participate in manufacturers' cooperative advertising programs. This leads to suboptimal outcomes if cooperative advertising programs are not enhanced by additional incentives (e.g., side payments or other services).